(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This article seeks to support the proposal of the stage RPG: a type of RPG and staging played on the theatrical stage in a spectacular way, based on tabletop RPG, conventional theater and puppet theater. The motivation for this research is based on doubts that settled in me during graduation and continue to be processed during postgraduate studies. Its theoretical basis starts from the study of the game as proposed by Huizinga, the act of playing being the origin of all archetypal activities of human culture, including games (and, in turn, RPGs) and theater. The stage RPG seeks to use animated forms as devices for connecting the two universes (real and ludic) to demonstrate the player-character and the fantastic-character on the scene, with the use of masks by the player-actors and with puppets, objects and shadows by the stage master.